Adaptive Position and Attitude Trajectory Tracking Control for a Quadrotor UAV - Tian, Yi-Xuan; Li, Chen; Yu, Wen-Tao; Xiong, Jing-Jing (2022 International Conference on Automation, Robotics and Computer Engineering (ICARCE), 2022)
The adaptive trajectory tracking control issue of a small quadrotor unmanned aerial vehicle (UAV) is preliminarily concerned and studied in this paper. The mathematic model of quadrotor UAV is firstly expressed in a simple form such that the model uncertainties and unknown external disturbances can be conveniently taken into account. Then, an adaptive sliding mode controller is developed for estimating model uncertainties and unknown external disturbances such that the robust and adaptive controller is obtained to enhance the robustness of the flight controller. It is found that the trajectories will asymptotically track the corresponding desired position and attitude values even under uncertainties and unknown disturbances. Finally, simulations based on the developed control scheme are conducted to demonstrate the effectiveness while faced with the uncertainties and unknown disturbances.